2021
DOI: 10.1016/j.echo.2020.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Trend of Global Longitudinal Strain in Takotsubo Cardiomyopathy and Clinical Predictors of Recovery

Abstract: As quoted in the letter by Hubert et al, 1 Owashi et al 3 recently proposed a very interesting mathematical model to derive with echocardiography specific LV pressure curves in patients with severe AS. Nevertheless, the proposed method also has some critical limitations: (1) it uses aortic valve area, among other parameters, to noninvasively predict the patient-specific LV pressure curve; however, calculation of aortic valve area with echocardiography has several known limitations 4 that can affect this estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A recent small study found clinically significant differences when patients with TTS were stratified by GLS recovery. 27 However, there were no differences in subsequent hospitalization and mortality between the groups in a short follow-up. When stratifying patients based on normalization of LVEF (>53%) or GLS (>18%), we found that a normalized GLS at follow-up was better able to discriminate prognosis in patients with TTS than LVEF.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A recent small study found clinically significant differences when patients with TTS were stratified by GLS recovery. 27 However, there were no differences in subsequent hospitalization and mortality between the groups in a short follow-up. When stratifying patients based on normalization of LVEF (>53%) or GLS (>18%), we found that a normalized GLS at follow-up was better able to discriminate prognosis in patients with TTS than LVEF.…”
Section: Discussionmentioning
confidence: 81%
“…A recent small study found clinically significant differences when patients with TTS were stratified by GLS recovery 27 . However, there were no differences in subsequent hospitalization and mortality between the groups in a short follow‐up.…”
Section: Discussionmentioning
confidence: 94%